Proceedings of the IEEE 2002 International Interconnect Technology Conference (Cat. No.02EX519)
DOI: 10.1109/iitc.2002.1014905
|View full text |Cite
|
Sign up to set email alerts
|

Packaging assessment of porous ultra low-k materials

Abstract: The need for lower effective dielectric constants for both inter-and intra-layer dielectrics is clearly stated in the International Technology Roadmap for Semiconductors (I).Recently some progress has been reported with regards to integration and reliability assessment of these new, relatively weak porous ultra low-k materials (2-4). Due to their mechanical weakness, these materials also present 'unique challenges to the packaging process. If no appropriate precautions are taken, the pans cannot be packaged at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In Cu CMP with low-k dielectrics, excess downforce during polishing can cause cracks or delaminations at the interfaces. 1,2) Recently, numerous works have been conducted on package-level chip integrity impact via the assembly and packaging of Cu/low-k systems. The mismatch of thermal expansion coefficients between the low-k films and the polyimide or molding compound causes the back-end layer to delaminate.…”
Section: Introductionmentioning
confidence: 99%
“…In Cu CMP with low-k dielectrics, excess downforce during polishing can cause cracks or delaminations at the interfaces. 1,2) Recently, numerous works have been conducted on package-level chip integrity impact via the assembly and packaging of Cu/low-k systems. The mismatch of thermal expansion coefficients between the low-k films and the polyimide or molding compound causes the back-end layer to delaminate.…”
Section: Introductionmentioning
confidence: 99%
“…A multi-level submodeling simulation technique has heen proposed to evaluate the impact of several important packaging parameters on low-k reliability [5]. An attempt to understand the feasibility of packaging of porous ultra low-k materials was reported [6]. Interfacial adhesion for CdSiLK interconnects under flip-chip packaging conditions was measured and compared with the crack driving force derived from 2D FEA model [7].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical examinations for the effect of matrial properties of components on reliability of solder bumps and Cu/low-K delamination were carried out by Lai et al [4] and Chen et al [5]. Following experimental investigations, Rasco et al [6] and Chen et al [5] demonstrated that proper selections of component materials can enhance the reliability of packages with Cu/low-K chips.…”
Section: Introductionmentioning
confidence: 99%